PRODUKTIVITAS PRIMER PERAIRAN KOLAM IKAN DI PERKEBUNAN KELAPA SAWIT DI DESA GUNUNG MELATI KECAMATAN BATU AMPAR KABUPATEN TANAH LAUT - Adelina Adelina; Mijani Rahman; Abdur Rahman (Fish Scientiae, 2019)
This research attempted to find out the level of primary aquatic productivity of fishpond in palm oil plantation in Gunung Melati Village Batu Ampar Subdistrict TanahLaut Regency and to find out the quality of water based on the abundance of plankton.The measurement of the primary productivity used combination of two oxygen methods, with drawal of sample of water, and plankton analysis. The result of the measurement wastabulated in form of table and described in form of graphic so that the difference in every observational station would be seen. Data analysis of primary productivity used oxygen measuring methods; those were dark bottle and clear bottle methods. The classification used for fertility level was according to Purnomo, et al, 1993. Result of the measurement showed that station 1 and station 2 had fertility level that belonged to trophic oligotrophic level (less fertile). Index value of plankton diversity in station 1 and station 2 were ranked not extremely low and belonged to minorcontaminated category.